A preliminary study on clinical profiles of dengue and dengue haemorrhagic fever suspected patients from two hospitals in the Western Province of Sri Lanka - PDNN Sirisena; F Noordeen; L Fernando (Sri Lankan Journal of Infectious Diseases, 2014)
Objective: Dengue fever (DF) is one of the most common public health problems in Sri Lanka. A pilot study was undertaken to investigate the clinical profiles of DF and dengue haemorrhagic fever (DHF) in patients admitted to two hospitals from July 2011 to July 2012. The objective of the study was to evaluate clinical patterns to improve pattern recognition and to determine whether these profiles have changed in recent times. Study design: The clinical profile was collected using a CDC style questionnaire and analyzed (Minitab, V14). Blood samples were collected from 50 patients from Gampaha and 204 patients from Negombo hospitals with a clinical suspicion of DF/DHF, between fever days 2 to 7. Laboratory data included a complete blood count (CBC) with haemoglobin, haematocrit, total leukocyte and platelet countsand liver function. CBC was repeated daily during the acute phase of the illness. Chest x-ray or ultrasound scanning was done to assess pleural and abdominal fluid accumulation. Results: The sample consisted of 168 (66.1%) males and 86 (33.8%) females. The age of the patients ranged from 6 months to 66 years with a mean of 12 (SD = 13.4). Fever was the major presenting complaint (100%) with headache in 90.1%. Retro orbital pain was present in 27.6% of patients and 78 % and 79.1 % experienced arthralgia and myalgia respectively. Rash and pleural effusion were present in 20% and 10.6 % respectively. Ascites and hepatomegaly were noted in 6.2% and 1.1%. Of the 254 patients, 69% had DF and 31% had DHF. The lowest WBC was 0.98 x 103/mL. Platelet count of <100,000 was seen in 65.3% cases. Only 35 patients (21 DF and 14 DHF) were tested for IgM/IgG. Based on these results, 38% (8/21) of DF cases were primary and 62 % (13/21) were either secondary or with past flavivirus infections. Primary dengue infection resulted in 43% (6/14) of DHF cases with 57% (8/14) resulting from secondary or with past flavivirus infections. Conclusion: The majority of clinically diagnosed dengue patients were males. The most common clinical feature was fever with headache, myalgia and arthralgia. DHF seemed to have occurred in both primary and secondary dengue infections. Some symptoms included in the WHO guidelines such as  rash, hemorrhagic manifestations and retro orbital pain were less commonly seen in the study. DOI: http://dx.doi.org/10.4038/sljid.v4i2.6941 Sri Lankan Journal of Infectious Diseases 2014; Vol.4(2):99-107